Peningkatan Kemampuan Berhitung Melalui Tabung Angka di TK Islam Ananda, Padang Pariaman - Ismawati, Iim (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
The object tives to be achieved in this study are to improve the numeracy skills of Muslim Kindegarten children from Lubuk Alung sub-district, Padang Pariaman district through tube numbers in group B2 with 15 student consisting of 10 girls and 5 boys. This type of research is classroom action researce. The aspect assessed are (1) children are able to say numbers 1-10 with a number tube, (2) children can connect numbers with objects throught a number tube, (3) children can connect the same number of objects through a number tube. The final result of research on numeracy in group B2 in ananda kindergarten Islam in sub district Lubuk Alung. Padang Pariaman district before this research was conducted were still low. This can be seen from the ability to count children in the category of very well developed and developed according to expectations obtained as much as 30% and after implementation of the action, the ability tu count children with tube numbers rose to 80%.